News Construction of the Corruption Eradication Commission's Sting Operation against Romahurmuziy: A Murray Edelman Framing Analysis of RMOL.co's March 2019 Coverage (Oratio Directa, 2020)
This study analyzes RMOL.co's construction of news concerning the Corruption Eradication Commission's sting operation against Romahurmuziy in March 2019. It uses a constructivist paradigm, a descriptive-interpretive qualitative approach, and Murray Edelman's framing model, which examines categorization, ideology, rubrication, and classification. The data consist of five purposively selected reports from RMOL.co's Law, Politics, and Headline sections. The findings show that RMOL.co tended to support the KPK's disclosure of the case. Its coverage emphasized the negative dimensions of Romahurmuziy's conduct and political position while constructing a positive image of the KPK and accommodating opposition narratives. The findings confirm that news construction does not merely present legal facts but also produces ideological emphases that shape public interpretations of political corruption and law-enforcement institutions.
Keywords: Framing analysis; Political corruption; Sting operation; Political actors; Political communication